TRADISI FENOK-FENOK DAN MELENG MANDRE LALENG BOCOK PADA PERNIKAHAN SUKU BUGIS MENURUT TOKOH AGAMA ISLAM TELUK PAKEDAI DUA - Sulianto, Agus; Marluwi, Marluwi; Muzammil, Sa'dullah (Al-Usroh, 2022)
The objectives of this study were: 1) To find out the implementation of the Fenok-Fenok and Meleng Mandre Laleng Bocok Traditions at the Bugis Tribe's traditional wedding in Teluk Pakedai Dua Village: 2) To find out the beliefs of the people of Teluk Pakedai Dua Village if the FenokFenok and Meleng Mandre Laleng Bocok Traditions in Bugis Tribe traditional marriages are not carried out: 3) To find out the views of religious leaders in Teluk Pakedai Dua Village about the Fenok-Fenok and Meleng Mandre Laleng Bocok Tradition at the Bugis Tribe of Teluk Pakedai Dua Village. This study uses a descriptive method with a qualitative approach in order to reveal the state of the research object as it is based on the data collected at the time the research was conducted. The data sources of this research consist of primary sources and secondary sources, namely: 1) The primary data used in this study is information on indigenous people and residents who have carried out the Fenok-Fenok Tradition and the Meleng Mandre Laleng Bocok Tradition in Teluk Pakedai District, Teluk Pakedai Dua Village: 2) Sources of secondary data are obtained from texts, marriage books, scientific journals, previous research, websites and the community of Teluk Pakedai Dua village. The data collection technique used by the researcher was in the form of interviews. To analyze the data, researchers used data reduction, data presentation, and conclusions. Based on the analysis conducted, the researchers concluded that: 1) The procedure in implementing the Fenok-Fenok and Meleng Mandre Laleng Bocok Tradition, the Bugis community of Teluk Pakedai Dua Village, has the potential to cause conflict in Islam which in the implementation of this tradition uses offerings, where these offerings have the potential to cause shirk when viewed from the point of view of Islamic law: 2) The belief of the Bugis people of Teluk Pakedai Dua Village has been passed down for generations in believing in the Fenok-Fenok and Meleng Mandre Laleng Bocok Tradition if they do not carry out this tradition, they will get interference from supernatural beings such as trance, and the appearance of spirits often occurs: 3) The views of religious leaders (Ustadz) of Teluk Pakedai Dua village on the Fenok-Fenok and Meleng Mandre Laleng Bocok Tradition do not conflict with Islamic law because everything depends on intentions. The impact of this research is expected to be a reference material and study material for the community and researchers who are in research.